A concise review of the natural existance, synthesis, properties, and applications of syringaldehyde - Bhawani, Showkat Ahmad; Mohamad Nasir, Mohamad Ibrahim; Sriprasanthi, R. B.; Shaharuddin, Shamsudeen; Farook, Adam (NC State University, 2012)
Syringaldehyde is a promising aromatic aldehyde that no longer deserves to remain in obscurity. It possesses worthy bioactive properties and is, therefore, used in pharmaceuticals, food, cosmetics, textiles, pulp and paper industries, and even in biological control applications. Mostly, the synthetic form of syringaldehyde is being used. This review serves as an appraisal of potential research and commercialization of naturally occurring syringaldehyde beyond the scope of the food and cosmetic industries. This article also provides a comprehensive account of the various conventional extraction and chromatographic techniques used in the separation, isolation, and quantification of syringaldehyde. Further, to understand this unique compound, a brief outline on the natural formation of syringaldehyde in lignin is accentuated in this article.